The Effect of Project Based Learning With Virtual Media Assistance on Student’s Creativity in Physics - Gunawan Gunawan; Hairunnisyah Sahidu; Ahmad Harjono; Ni Made Yeni Suranti (LPMPP Universitas Negeri Yogyakarta, 2017)
Abstract: Physics learning should be able to provide opportunities for learners to be creative in understanding the things that learned. One of the efforts made to improve the quality of physics learning was to apply the model of project based learning with virtual media. This study aimed to examine the effect of virtual media-aided model toward students’ creativity. This quasi experimental study used pretest-posttest control group design. The research instrument used a verbal and figural creativity test which had been validated by experts. Hypothesis test used employed variance test. The increase in creativity was determined based on the results of the N-gain test. The results showed that there was an increase of students' creativity in both classes. The experiment class had a higher creativity increase than the control class. Verbal and figural creativity improved in both classes. Verbal creativity increased higher than figural creativity. This shows that the model of project based learning with virtual media that applied successfully improve the students’ creativity in physics learning.EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA VIRTUAL TERHADAP KREATIVITAS FISIKA PESERTA DIDIK Abstrak: Pembelajaran fisika seharusnya mampu memberikan peluang bagi peserta didik untuk berkreasi dalam memahami hal yang dipelajari. Salah satu upaya yang dilakukan untuk meningkatkan kualitas pembelajaran fisika adalah dengan menerapkan model project based learning berbantuan media virtual. Penelitian ini bertujuan menguji pengaruh model berbantuan media virtual terhadap kreativitas peserta didik. Penelitian kuasi eksperimen ini menggunakan pretest-posttest control group design. Instrumen penelitian menggunakan tes kreativitas verbal dan figural yang telah divalidasi oleh para ahli. Uji hipotesis menggunakan uji t polled varian. Peningkatan kreativitas ditentukan berdasarkan hasil uji N-gain. Hasil penelitian menunjukkan adanya peningkatan kreativitas peserta didik pada kedua kelas. Kelas eksperimen mengalami peningkatan kreativitas yang lebih tinggi dibandingkan kelas kontrol. Kreativitas verbal dan figural mengalami peningkatan pada kedua kelas. Kreativitas verbal meningkat lebih tinggi dibandingkan kreativitas figural. Hal ini menunjukkan bahwa model project based learning berbantuan media virtual yang diterapkan berhasil meningkatkan kreativitas peserta didik dalam pembelajaran fisika.